Long-term follow-up of the incidence of Helicobacter pylori. (September 2018) - Rowland, M.; Clyne, M.; Daly, L.; O'Connor, H.; Bourke, B.; Bury, G.; O'Dowd, T.; Connolly, L.; Ryan, J.; Shovlin, S.; Dolan, B.; Drumm, B.
Abstract: Objectives: Helicobacter pylori causes peptic ulcer disease and gastric cancer. Understanding the incidence of H. pylori could help guide research on potential infection prevention strategies. Previous studies indicate infection occurs in young children, but the risk of infection in older children and adolescents is unclear. Our hypothesis was that H. pylori infection is rare in adolescence or adulthood. Our aim was to determine the incidence of H. pylori over a prolonged follow-up in a cohort of 626 noninfected individuals. Methods: Participants, including index children, mothers, fathers and siblings, from a previous study (1997–2002) were traced, and 883 of 946 participated in this extended follow-up. We used the 13 C urea breath test ( 13 C-UBT) to determine the incidence of H. pylori among 626 family members not infected in 2002, including 75 younger siblings who were not born or too young for testing in 2002. Results: Eight (3.8%) of 210 index participants (mean ± standard deviation age 17.92 ± 0.77 years) became infected during 11.07 ± 0.56 years of follow-up (incidence, 3.42 per 1000 person-years; 95% confidence interval (CI), 1.48–6.74). Only one (0.6%) of 165 older siblings became infected (incidence, 0.57 per 1000 person-years; 95% CI, 0.007–3.16) and one of 176 parents became infected (incidence, 0.63 per 1000 person-years; 95% CI, 0.01–3.5). Of 75 younger siblings (age 10.9 ± 2.85 years) who were too young for testing or not yet born in 2002, nine (12%) became infected (incidence, 11.32 per 1000 person-years; 95% CI, 5.27–21.49). The highest incidence of H. pylori infection was in those born after 2005. Conclusions: The incidence of H. pylori was extremely low in older children and adults in developed countries. Spontaneous clearance of infection was uncommon in our study population.